2021
DOI: 10.47405/mjssh.v6i1.624
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Job Motivation on Job Satisfaction: A Case Study of Polytechnic Academic Staff

Abstract: Job motivation plays a vital role in determining job satisfaction levels. In the Malaysian Polytechnic context, limited studies have investigated the influence of job motivation on job satisfaction among academic staff. Therefore, this study aims is to examine the influence of job motivation on job satisfaction among polytechnic academic staff. This study employs quantitative research and single-cross sectional study. The data is gathered using the survey method. The result of multiple regression analysis show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 25 publications
1
7
0
1
Order By: Relevance
“…It exemplifies an individual's willingness to take risks to achieve a specific goal, whereas direction is the channel for intensity toward the correct objective, and persistence is the duration someone maintains an effort to achieve a specific goal (Fuller et al, 2008). Previous studies were done to investigate the role of motivation based on different samples like 103 non-academic staffs grade N17 of Universiti Teknologi Malaysia (Ghaffari et al, 2017), 218 female employees of several economic sectors of Malaysia, namely manufacturing, education, hospitality, and health (Kamaruddin et al, 2017), and 108 academic staffs of Polytechnics in Malaysia (Omar et al, 2021). The findings reported that motivation is a significant predictor of employees' performance (Ghaffari et al, 2017;Kamaruddin et al, 2017;Omar et al, 2021).…”
Section: Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…It exemplifies an individual's willingness to take risks to achieve a specific goal, whereas direction is the channel for intensity toward the correct objective, and persistence is the duration someone maintains an effort to achieve a specific goal (Fuller et al, 2008). Previous studies were done to investigate the role of motivation based on different samples like 103 non-academic staffs grade N17 of Universiti Teknologi Malaysia (Ghaffari et al, 2017), 218 female employees of several economic sectors of Malaysia, namely manufacturing, education, hospitality, and health (Kamaruddin et al, 2017), and 108 academic staffs of Polytechnics in Malaysia (Omar et al, 2021). The findings reported that motivation is a significant predictor of employees' performance (Ghaffari et al, 2017;Kamaruddin et al, 2017;Omar et al, 2021).…”
Section: Motivationmentioning
confidence: 99%
“…To boost their confidence, they need some sort of motivation for them to carry on with their job of which the management should care about. Few recent studies have highlighted the contribution of motivation on performance (Ghaffari et al, 2017;Kamaruddin et al, 2017;Omar et al, 2021). From the Islamic point of view, a business would be successful if it follows the teaching of Islam, in which the Muslim workers are allowed to perform their religious duty such as prayer to earn barakah in their daily job.…”
Section: Introductionmentioning
confidence: 99%
“…Motivasi yaitu gerakan atau dorongan yang kuat agar individu mau melakukan ataupun mengerahkan seluruh kompetensi dan ketrampilan yang dimilikinya untuk segera menyelesaikan tugas atau kegiatan yang dibebankan kepadanya dan menjadi tanggung jawab (Firdaus et al, 2017). Motivasi juga dapat didefinisikan sebagai awal proses aktivitas individu, yang diarahkan untuk mencapai tujuan tertentu untuk memenuhi kebutuhan (Omar et al, 2021). Pekerjaan yang dilakukan oleh pemimpin atau manajer yaitu memotivasi karyawannya dalam bentuk penyampaian ide dan inspirasi, pemberian semangat serta dukungan untuk mengambil keputusan tertentu (Erwatiningsih, 2017).…”
Section: Motivasi Kerjaunclassified
“…When employees are dissatisfied, the tendency for them to leave the company is high or they will remain working there but contribute passively to help the organizations thrive (Huynh, 2020). Similarly, dissatisfied employees may have disruptive impacts on organization for example, issues of unemployment and absenteeism which are caused by their lack of motivation, and underperform (Omar et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Most previous studies only focused on job satisfaction which influenced by motivation, such as among the professional occupations i.e., accountants (Asaari et al, 2020), quantity surveyors (Nur et al, 2018) and academic staffs (Tentama et al, 2020;Omar et al, 2021) or the influence of job satisfaction by emotional intelligence (Mohammadi & Yekta, 2018;Javed et al, 2020). To date, there is no study that combine the two variables (i.e., motivation and emotional intelligence) in particular among female non-academics at the higher learning institutions.…”
Section: Introductionmentioning
confidence: 99%